Resilience for activity engagement among frail older adults: moderated mediation effect of social support - Eunna Oh; Nayoung Kim; Lkhagvajav Gansukh; Rhayun Song (BMC Psychology)
Abstract Background Frailty in older adults increases vulnerability to stressors, contributing to adverse outcomes such as falls, hospitalizations, and disability. Resilience has been identified as a protective factor that supports physical function, cognitive health, and independence in daily activities. This study aimed to examine the direct and indirect effects of resilience on daily activity engagement, with subjective cognition as a mediator and social support as a moderator. Methods A secondary data analysis was conducted with a convenience sample of 397 frail, community-dwelling older adults drawn from a national survey. A moderated mediation model was tested using SPSS and the PROCESS macro (Model 14, version 4.3). Age (treated as a continuous variable) and sex (dummy-coded, with male as the reference group) were included as covariates due to their previously established associations with daily activity engagement. Results A total of 212 women and 185 men participated in this study with a mean age of 73.51 years (SD = 6.48). Resilience has a significant direct effect on daily activity engagement (β = 0.57, t = 4.99, p < 0.001). The standardized regression coefficient decreased from 0.57 to 0.41 (t = 3.51, p < 0.001) when subjective cognition was included in the model, confirming the partial mediating effect. In the moderation model, resilience (β = 0.34), subjective cognition (β = 0.38), and social support (β = 0.29) were significant predictors of daily activity engagement. The interaction effect between subjective cognition and social support was significant (β = 0.04, BootCI 0.01, 0.08), showing that subjective cognition significantly predicts daily activity engagement only when specific levels of social support are present. The moderated mediation index was small but significant (β = 0.02, BootCI [0.001, 0.03]), even after controlling for age and sex. Conclusion This study identified resilience, subjective cognition, and social support as essential factors in promoting daily activity engagement among frail older adults. The role of social support as moderator was confirmed in helping older adults maintain their independence through enhanced resilience and subjective cognition. Further research should explore the broader aspects of social support to fully understand its impact on active aging dynamics.